Analysis of the echogenicity and echotexture of the walls of the palmar and plantar digital arteries of horses and mules - Fogaça, Jéssica Leite [UNESP]; Castiglioni, Maria Cristina Reis [UNESP]; de Campos Vettorato, Michel [UNESP]; de Melo Neto, Gabriel Barbosa [UNESP]; de Moraes, Alessandra Regina Dhom Pimentel [UNESP]; Filadelpho, André Luis [UNESP]; Filho, José Nicolau Prospero Puoli [UNESP]; Machado, Vânia Maria Vasconcelos [UNESP] (Universidade Federal do Paraná, 2023)
The grayscale histogram (GH) is a tool available in some software that allows evaluating the quantity and distribution of the grayscale frequency of certain region studied in an image. In ultrasonography, GH has been applied to assess the echogenicity and echotexture of different organs, revealing clinical applicability. This study makes a comparative analysis of the echogenicity and echotexture of the palmar and plantar digital arteries in healthy horses and mules using the grayscale histogram (GH). It also set out to compare the possible variability between the superficial and deep tunica intima and media (IM) of the vessels evaluated. B-Mode ultrasonography was performed in the longitudinal plane of the lateral and medial palmar and plantar digital arteries in 10 healthy horses and 10 mules. Subsequently, the images were analyzed using the GH tool to acquire the variables Mean (echogenicity) and Standard deviation (StdDev) (ecotexture). It was observed that mules showed higher values of brightness intensity (Mean) than horses. Differences were observed between superficial and deep IM, and the deep wall showed higher echogenicity and heterogeneity in both the equine species and in the mule hybrid. The GH proved to be a viable tool to quantify the echogenicity and echotexture of the walls (superficial and deep) of the palmar and plantar digital arteries of horses and mules. In addition, it allowed to highlight the differences found between animals (horses and mules) and IM (superficial and deep).
Keywords: grayscale histogram; IM; ultrasound